Prevalence of Stunting and Associated Factors among Under Five Children in Wondo Genet Woreda, Sidama Zone, Southern Ethiopia - Woldie, Yadessa Tegene; Belachew, Tefera; Hailu, Dejene; Teshome, Tesfalem; Gutema, Hordofa (International Journal of Medical and Health Sciences Research, 2014)
Background: Stunting is a serious health problem and deep rooted in southern Ethiopia of poor diet, in adequate food intake, disease burden, population growth, poor health service delivery and repeated drought. Objective: to assess the prevalence of stunting and associated factors among under five year’s old children in the study area. Methods: This cross sectional study was conducted in Wondo Genet Woreda from February, 25 to March 15, 2011. The sample size was determined using formula for estimating single population proportion. The sample size was determined using formula for estimating single population proportion. Three Kebele’s were selected by stratified two stage cluster sampling method and study households were identified by simple random sampling technique from each ‘Kebele. The data was analyzed using SPSS v.16.0 statistical software version16.0. For all statistical significance tests, the cut- off value set will be p<0.05 with CI of 95%. Results: Out of 576 study participants 50.3% were stunted. Stunting was 3.1times more common in households where decision was made by husband only (P=0.001), paternal education level of 7-8 grade was 2.29 times the contributing factor of stunting [AOR= 2.29, 95% CI: 1.15-4.54]. Children who did not eat vegetable source foods were 2.54 times more likely to be stunted [AOR= 2.54, 95% CI: 1.20-5.37]. Conclusion and Recommendation: Prevalence of stunting in Wondo Genet Woreda is similar when compared to the national figure and among female and male participants. Home delivery was found to be the protective factors of stunting and similar impact was seen by displacement from usual residence. Thus the community based nutrition program for prevention and early detection of stunting should be strengthened.